2007
DOI: 10.1086/513462
|View full text |Cite
|
Sign up to set email alerts
|

The Ages and Masses of Lyα Galaxies atz∼ 4.5

Abstract: We examine the stellar populations of a sample of 98 z ∼ 4.5 Lyman alpha emitting galaxies using their broadband colors derived from deep photometry at the MMT. These galaxies were selected by narrowband excess from the Large Area Lyman Alpha survey. Twenty-two galaxies are detected in two or more of our MMT filters (g', r', i' and z'). By comparing broad and narrowband colors of these galaxies to synthetic colors from stellar population models, we determine their ages and stellar masses. The highest equivalen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
183
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(202 citation statements)
references
References 52 publications
18
183
1
Order By: Relevance
“…At even higher redshift, Pirzkal et al (2007) showed that a sample of 4 < z < 5.7 Lyα emitters had very young ages of a few Myr and small stellar masses, in the range 10 6 −10 8 M . These results agreed well with those of Finkelstein et al (2007), who studied almost 100 Lyα emitters at z = 4.5. Finkelstein et al (2008) reported, studying a different sample, finding very dusty, massive galaxies with A 1200 as high as 4.5 mag and masses as high as several ×10 10 M , at z = 4.5.…”
Section: Datesupporting
confidence: 92%
See 1 more Smart Citation
“…At even higher redshift, Pirzkal et al (2007) showed that a sample of 4 < z < 5.7 Lyα emitters had very young ages of a few Myr and small stellar masses, in the range 10 6 −10 8 M . These results agreed well with those of Finkelstein et al (2007), who studied almost 100 Lyα emitters at z = 4.5. Finkelstein et al (2008) reported, studying a different sample, finding very dusty, massive galaxies with A 1200 as high as 4.5 mag and masses as high as several ×10 10 M , at z = 4.5.…”
Section: Datesupporting
confidence: 92%
“…Objects with large equivalent widths (EWs) are thus selected by comparing the colours in the narrow-band image and complementary broad-band images. Spectroscopically confirmed Lyα emitters now include several hundreds of sources at redshifts z ∼ 3 (e.g., Møller & Warren 1993;Cowie & Hu 1998;Steidel et al 2000;Fynbo et al 2001Fynbo et al , 2003aMatsuda et al 2005;Venemans et al 2007;Nilsson et al 2007;Ouchi et al 2008), z ∼ 4.5 (Finkelstein et al 2007), z ∼ 5.7 (Malhotra et al 2005;Shimasaku et al 2006;Tapken et al 2006) and z ∼ 6.5 (Taniguchi et al 2005;Kashikawa et al 2006). However, in the low redshift range, between z ≈ 1.6 corresponding to the atmospheric cut-off in the UV and z ∼ 3, little progress has been made.…”
Section: Introductionmentioning
confidence: 99%
“…At the redshift of the burst, the Ly-α luminosity is 4.3×10 42 erg s −1 . This value is in the range of luminosities of other LAEs identified by dedicated surveys at z ∼ 4.5 (Finkelstein et al 2007;Shioya et al 2009;Wang et al 2009). In particular, Shioya et al (2009), in a survey of z ∼ 4.8 LAEs in the COSMOS two square degree field, computed the Ly-α luminosity function of these objects, measuring L = 8 +17 −4 × 10 42 erg s −1 .…”
Section: Grb Hostmentioning
confidence: 52%
“…By now, several hundreds of Lyα emitters (LAEs) have been detected through narrow-band imaging at z = 0.3−7.7 (e.g. Møller & Warren 1993;Fynbo et al 2003;Gronwall et al 2007;Venemans et al 2007;Nilsson et al 2007;Finkelstein et al 2007;Ouchi et al 2008;Grove et al 2009;Hibon et al 2010). Lyα emission may be generated by three main mechanisms: i) the ionising flux of O and B stars indicative of star formation; ii) the ionising flux of an energetic UV source, e.g.…”
Section: Introductionmentioning
confidence: 99%